Bromodomain proteins as potential therapeutic targets for B-cell non-Hodgkin lymphoma - Dan Zou; Sitong Feng; Bowen Hu; Mengya Guo; Yan Lv; Rong Ma; Yuxin Du; Jifeng Feng (Cell & Bioscience)
Abstract Background B-cell non-Hodgkin lymphoma (B-NHL) is the most common type of lymphoma and is significantly heterogeneous among various subtypes. Despite of considerable advancements in treatment strategies for B-NHL, the prognosis of relapsed/refractory patients remains poor. Main text It has been indicated that epigenetic dysregulation is critically associated with the pathogenesis of most hematological malignancies, resulting in the clinical targeting of epigenetic modifications. Bromodomain (BRD) proteins are essential epigenetic regulators which contain eight subfamilies, including BRD and extra-terminal domain (BET) family, histone acetyltransferases (HATs) and HAT-related proteins, transcriptional coactivators, transcriptional mediators, methyltransferases, helicases, ATP-dependent chromatin-remodeling complexes, and nuclear-scaffolding proteins. Most pre-clinical and clinical studies on B-NHL have focused predominantly on the BET family and the use of BET inhibitors as mono-treatment or co-treatment with other anti-tumor drugs. Furthermore, preclinical models of B-NHL have revealed that BET degraders are more active than BET inhibitors. Moreover, with the development of BET inhibitors and degraders, non-BET BRD protein inhibitors have also been designed and have shown antitumor activities in B-NHL preclinical models. This review summarized the mechanism of BRD proteins and the recent progress of BRD protein-related drugs in B-NHL. This study aimed to collect the most recent evidences and summarize possibility on whether BRD proteins can serve as therapeutic targets for B-NHL. Conclusion In summary, BRD proteins are critical epigenetic regulatory factors and may be potential therapeutic targets for B-NHL.